Sress-corrosion cracking under cathodic protection of low alloy steel joints with high frequency weld and arc weld - Nyrkova, L.I.; Goncharenko, L.V.; Osadchuk, S.O.; Prokopchuk, S. M.; Klymenko, A.V.; Kostin, V.A. (Physics and Chemistry of Solid State, 2022)
According to the results of complex electrochemical, corrosion-mechanical and fractographic studies, the existence of three potential regions, in which the stress-corrosion cracking (SCC) of 17G1S (17G1S-U) steel in the NS4 model soil electrolyte occurs by different mechanisms was established and experimentally confirmed: at potentials positively than -0.8 V – by the mechanism of local anodic dissolution, at potentials region from -0.8 V to -0.98 V – by the mixed mechanism, at potentials less than -0.98 V by hydrogen breaking mechanism. The susceptibility to SCC of high-frequency weld joints, estimated by the coefficient of KS, in the potential range from the corrosion potential to -1.2 V increases (KS increases from 1.1 to 1.8), which is less intense than for steel 17G1S/17G1S-U (KS increases from 1.1 to 2.8), for arc weld joints – does not change much enough (KS increases from 1.1 to 1.3). The validity of KS coefficient introduced for the base metal for comparative assessment of the susceptibility to SCC of welded joints, is provided in case that there are no defects in the welds and SCC occurs on base metal.